2018
DOI: 10.1016/j.jacc.2018.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Rates Following Surgical Versus Percutaneous Coronary Revascularization

Abstract: This individual patient-data pooled analysis demonstrates that 5-year stroke rates are significantly lower after PCI compared with CABG, driven by a reduced risk of stroke in the 30-day post-procedural period but a similar risk of stroke between 31 days and 5 years. The greater risk of stroke after CABG compared with PCI was confined to patients with multivessel disease and diabetes. Five-year mortality was markedly higher for patients experiencing a stroke within 30 days after revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 33 publications
2
53
2
2
Order By: Relevance
“…While some other studies showed that CABG resulted in significantly higher rates of stroke than PCI for LM or multivessel disease [3], we found that the difference in rates was indistinctive. e mechanisms underlying the increased risk of stroke with CABG are likely multifactorial.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…While some other studies showed that CABG resulted in significantly higher rates of stroke than PCI for LM or multivessel disease [3], we found that the difference in rates was indistinctive. e mechanisms underlying the increased risk of stroke with CABG are likely multifactorial.…”
Section: Discussioncontrasting
confidence: 97%
“…Coronary artery bypass graft (CABG), as an effective treatment for CAD, has been introduced for more than 50 years, and it is currently the preferred modality for treating complex CAD [1,2]. However, over the last twenty years, there have been significant advances in percutaneous coronary intervention (PCI) from the era of balloon angioplasty and subsequent bare-metal stents to drug-eluting stents (DESs) [3]. With improving technology and techniques for PCI, such as adjunctive antithrombotic drugs, periprocedural management, and the experience of interventional cardiologists, research has focused increasingly on more complex diseases, such as LM disease and multivessel disease.…”
Section: Introductionmentioning
confidence: 99%
“…313 After 30 days, stroke rates between revascularization techniques were similar in a recent individual patient data meta-analysis of 11 randomized trials. 313 Ischaemic stroke after CABG is multifactorial: thrombo-embolism from the aorta, its branches, or the heart; atrial arrhythmias; inflammatory pro-thrombogenic milieu; lower levels of antiplatelet therapy perioperatively; and haemodynamic instability. However, the most consistent predictor of perioperative stroke is previous stroke or TIA.…”
Section: Prevention Of Stroke Associated With Carotid Artery Disease mentioning
confidence: 91%
“…A landmark analysis of the whole population (with or without DM) suggested that the increased risk of stroke after CABG is more pronounced in the first 30 days after the procedure. Stroke rates from day 31 to 5 years were comparable between PCI and CABG groups (15). Arterial conduits have better long-term patency when compared with venous grafts, but the use of bilateral internal mammary artery grafts in patients with DM is still debatable, given the concerns of sternal wound infection (16).…”
Section: Multivessel Diseasementioning
confidence: 96%
“…When compared with CABG, PCI was associated with a higher likelihood of 5-year all-cause mortality in patients with DM and MVD (n¼3,266 patients; hazard ratio [HR], 1.48; 95% CI, 1.19 to 1.84; p¼0.0004) (14). Conversely, PCI was associated with significantly lower 5-year stroke rates compared with CABG, especially in patients with DM (HR, 0.52; 95% CI, 0.37 to 0.75; p<0.001; p¼0.004 for interaction) (15). A landmark analysis of the whole population (with or without DM) suggested that the increased risk of stroke after CABG is more pronounced in the first 30 days after the procedure.…”
Section: Multivessel Diseasementioning
confidence: 99%